ENERGY EFFICIENCY IN THE SHIPPING SECTOR – A CASE STUDY - BRANISLAV DRAGOVIŠ; ERNESTOS TZANNATOS; VASSILIS ΤSELENTIS; AMALIA-VENERA TODORUT (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2017)
The improvement of Ship Energy Efficiency has been a major issue for the Shipping industry, primarily for three reasons; Firstly because fuel expenses of merchant ships contribute substantially to the overall expenses, secondarily, as conventional diesel engines and gas turbines emit large amounts of Greenhouse Gases (GHGs), contributing to the Climate Change and thirdly due to recent legislation including IMO Resolutions and EU Directives. The above in addition to the recent economic recession, have made it imperative for the industry to lower costs and introduce novel technologies and technical innovations, through the application of the Energy Efficiency Design Index (EEDI) and Energy Efficiency Operation Index (EEOI).This paper aims to contribute to the identification of methods and management tools in order to improve energy efficiency, by developing Ship Energy Efficiency Management Plans (SEEMPs). The paper focuses especially on investments, modifications, management and operational changes that can be deployed, in order to improve energy efficiency of existing ships. Finally, the economic result of modifications made on an existing vessel is presented, using data from a study performed by the authors in collaboration with several shipping companies.